Gender and Development Policies in Aviation: A Systematic Literature Review - Gonzalo, Jonah; Dumdumaya, Ma. Theresa; Binay, Marites; Fanoga, Shella; Gomez, Ma. Jinky (PT. Riset Press International, 2026)
This literature review examines gender and development policies within the aviation sector. This paper gives emphasis to the persistent disparities and evaluating policy frameworks that aim to promote equity and inclusion. With a systematic review framework, relevant peer-reviewed literature, industry reports, and policy documents to capture data regarding the workforce representation, organizational culture, and regulatory practices, data was synthesized. Findings suggest significant underrepresentation of women and these are particularly in technical and leadership roles which are driven by socio-cultural barriers, organizational biases, and policy implementation gaps. The findings imply that the underrepresentation of women in technical and leadership positions is a result of socio-cultural factors, organizational discrimination, and inadequate policy implementation. In contrast, high-level standards of governance and weaker shadowing frameworks, ICAO, IATA and UNWTO do all exhibit gender-friendly governance strategies. This paper brings to light the need for holistic approaches through which intervention policy, inclusive leadership, technology reform and governance participation can take root. Suggestions are made to establish strong evaluation systems, advance stakeholder cooperation and interplay, and furthering gender sensitive strategies in sustainability plans in order to build a balanced and flexible aviation workforce.